Draft Genome Sequence of Rhodobacteraceae Strain PD-2, an Algicidal Bacterium with a Quorum-Sensing System, Isolated from the Marine Microalga Prorocentrum donghaiense - Zheng, Li (Genome Announc, 2015)
Rhodobacteraceae strain PD-2 was isolated from the marine microalga Prorocentrum donghaiense. It has algicidal activity toward its host and could produce N-acylhomoserine lactone signals. Here, we present the draft genome of strain PD-2, which contains 5,227,214 bp with an average GC content of 66.19%. There were 4,864 encoding gene sequences and two clusters of luxI and luxR homologues identified.